DEVELOPMENT OF GREEN CHEMISTRY LEARNING MODULE INTEGRATED WITH CO-CURRICULAR PROJECTS TO IMPROVE THE QUALITY OF HIGH SCHOOL GRADUATES - Cyntia Widi Udya; Rayandra Asyhar; M. Naswir (SOSIOEDUKASI, 2026)
This research aims to develop an integrated green chemistry learning module for co-curricular projects to improve the quality of high school graduates which includes mastery of knowledge, process and practice skills, Higher Order Thinking Skills (HOTS), attitudes and character, as well as 21st century competencies in the form of science literacy, numeracy, and digital literacy. The research is motivated by the still dominance of chemistry teaching materials that are oriented to theoretical concepts and have not been much associated with environmental issues or project activities that support the overall development of graduate quality. The research uses the Research and Development method with the ADDIE Branch model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects involved material experts, media experts, chemistry teachers, and students of class X Phase E of SMA Negeri 2 Jambi City. Data was collected through interviews, questionnaires, expert validation, student responses, and graduate quality tests, then analyzed descriptively, quantitatively and qualitatively. The results of the study show that the modules developed have contextual, innovative, and project-based characteristics and are classified as very feasible and excellent according to experts, teachers, and students. The effectiveness test showed a significant difference between the results of the pre-test and post-test with an N-Gain value of 0.7130 which was included in the medium category, so that the module proved to be quite effective in improving the quality of student graduates.